Experimental Analysis of Vibration and Noise Characteristic of Helical Gear with Nano-lubricant Additive - Kai Xu; Xudong Cheng; Mingyuan Wu; Yanling Zhang; Xiaozhong Deng; Huiliang Wang; Xiaoling Gou (Jixie chuandong)
Based on the analysis of the physicochemical characteristics of nano-ZrO2， SiC， SiO2， and Al2O3， the vibration and noise characteristics of lubricating oils containing ZrO2， SiC， SiO2， and Al2O3 additives on helical gears are investigated. The current 20CrMnTi helical spur gears are tested. Routine lubrication and lubricity with nano additive lubricants are applied. By applying different loads and speeds to helical gears， the vibration and noise characteristics of helical gears under different working conditions and different lubrication methods are analyzed. Effect of nano additive lubricant on gear vibration and noise is analyzed. The results show that the nano additive lubricant can effectively reduce the vibration and noise values of the helical gear under different working conditions in a relatively short period of time， especially for the axial vibration reduction effect is more obvious than the radial direction. On the basis of this， the sensitivity of the gear damping effect to the load and rotation speed under the lubricant additive method of nano additive is further analyzed， and it is found that the nano additive lubricant oil has more sensitivity to the rotation speed of the gear.